Fabrication and Characterization of Environmentally Friendly Bioplastic Film Based on Chitosan from Cassava Peel Starch - Muhammad Fahmi Reza; Akhmad Irfan; M Furqon Hakim; Kristya Hadi Wicaksono; Vishal R. Panse; Alok Shukla (International Journal of Hydrological and Environmental for Sustainability, 2025)
Bioplastics are renewable materials capable of natural degradation and can be synthesized using bio-organic compounds such as cellulose, chitosan, carboxymethyl cellulose (CMC), and glycerol. Cassava peels, an agricultural byproduct, are a rich source of starch and cellulose, making them a promising raw material for bioplastic production. This study aims to fabricate and characterize chitosan-based bioplastic films using cassava peel starch, with a focus on optimizing their mechanical and biodegradation properties. Bioplastic films were prepared by combining cassava peel starch, chitosan, CMC, and glycerol, with chitosan concentrations varied at 45% and 75%. The films were evaluated for surface morphology using Scanning Electron Microscopy (SEM), tensile strength, elongation at break, water absorption capacity, and biodegradability. SEM analysis revealed that chitosan concentration significantly influenced the film morphology, which in turn affected mechanical and swelling properties. The highest tensile strength (0.07 MPa) and elongation (22.5%) were observed in films with 75% chitosan. Water absorption peaked at 93.32% for the same formulation. Biodegradability tests showed complete degradation (100%) within 12 days for films with 45% chitosan. These findings demonstrate that cassava peel starch combined with chitosan can produce biodegradable films with tunable properties, offering a sustainable alternative for packaging and other applications.